Thoracoscopic examination of empyema in a patient with sparganosis mansoni. Issue 2 (February 2016) - Takeda, Keita; Suzuki, Junko; Nagai, Hideaki; Watanabe, Kaoru; Yokoyama, Akira; Ando, Takahiro; Suzuki, Jun; Ohshima, Nobuharu; Masuda, Kimihiko; Tamura, Atsuhisa; Akagawa, Shinobu; Kitani, Masashi; et al.
Abstract: A 27-year-old man was admitted to our hospital with right pleural effusion. He had suffered from right chest and back pain and a high fever for one week prior to the admission. He had been treated with clarithromycin without improvement. Since thoracoscopy under local anesthesia revealed purulent effusion, synechiae and fibrous septa in the thoracic cavity, synechiotomy was performed and we started antibiotic treatment with the diagnosis of acute bacterial empyema. At the same time, we also suspected parasitic infection because of massive eosinophilic infiltration in pleural effusion and his dietary history of eating raw frogs. During the course of the disease, he had an infiltration in the right lower lobe and pneumothorax. Finally, we diagnosed him with sparganosis mansoni because his serum as well as pleural effusion was positive for the binding to sparganosis mansoni plerocercoid antigen, without any positive findings in bacteriology. His pleural effusion and lung infiltration were resolved after the administration of a high-dose praziquantel. We report this rare parasitic empyema with findings by thoracoscopic examination.